Mnestic functions restoration due to chronic brain ischemia pathogenetically oriented pharmacocorrection as a condition to enhance cerebral resistance - Myronov, O. (Journal of Education, Health and Sport, 2025)
The purpose of the study was to investigate the efficacy of separate and combined administration of pentoxifylline, memantine and xavron in the pharmacological correction of cognitive impairment in rats under conditions of experimental chronic brain ischemia. The experimental trials were performed in conditions of chronic brain ischemia in 80 male rats. Animals were observed during 7 days after carotid artery ligation. The processes of learning, short-tern and long-term memory expression together with conditioned reflexes extinction were determined 1, 3, 5 and 7 days from the beginning of the trials. The efficacy of neuroprotection in case of endonasal pentoxifylline and i.p. memantine and xavron separate and combined administration was evaluated in the modeled conditions. Rats with chronic brain ischemia were shown to develop mnestic disturbances, and their severity is time-dependent. The severity of the developed cognitive disorders is characterized by impairment of learning processes and of short- and long-term memory functioning. The positive effects of separate and combined use of pentoxifylline, memantine, and xavron under chronic brain ischemia conditions contributed to restoration of mnestic disturbances. The efficacy of the tested neuroprotection regimens under the experimental conditions was dependent on the duration of the post-ischemic period and on the routes of administration of the pharmacological agents. The most effective method of pharmacological correction of cognitive disorders under chronic brain ischemia conditions is combined pentoxifylline+ memantine administration as well as pentoxifylline+ xavron administration. The third place in terms of neuroprotective efficacy is occupied by endonasal pentoxifylline administration. The nootropic efficacy of these treatment regimens was recorded as early as Day 3 of the experiment and persisted until the end of the experiment. The author conclude that a number of functional disturbances established under chronic brain ischemia conditions constitute evidence of weakened cerebral resistance and an impetus for developing a comprehensive pathogenetically oriented correction of the formed disorders aimed at eliminating the developed disturbances and restoring cerebral resistance. He is confident that the nootropic efficacy of separate and combined administration of pentoxifylline, memantine and xavron in conditions of chronic brain ischemia enhances cerebral resistance, restores mnestic disturbances manifested by impairment of memory engram formation and retention, and serves as an experimental basis for the expediency of clinical testing of comprehensive pathogenetically substantiated correction of mnestic disorders in a large contingent of patients with chronic ischemia.